Evaluation of the video use as a complementary teaching tool in the health courses of the central west of Brazil region (Research, Society and Development, 2020)
The aim of this study was to evaluate whether health courses of the Central-West region of Brazil offer educational videos as a complementary teaching tool and to analyse whether the characteristics of the videos influence user engagement. The e-mec platform databank was used to access information from 295 health courses. Simultaneously, basic histology videos were created and offered freely on YouTube. It was observed that there is a demand for free health educational videos. However, no videos were found on health courses websites. It was found that videos of up to 1 min present better user retention (83%) than longer videos (58%) and that smartphones are not the preferred device to access educational videos online (p